Belowground impacts of alpine woody encroachment are determined by plant traits, local climate, and soil conditions. (8th October 2020) - Collins, Courtney G.; Spasojevic, Marko J.; Alados, Concepción L.; Aronson, Emma L.; Benavides, Juan C.; Cannone, Nicoletta; Caviezel, Chatrina; Grau, Oriol; Guo, Hui; Kudo, Gaku; Kuhn, Nikolas J.; Müllerová, Jana; et al.
Abstract: Global climate and land use change are causing woody plant encroachment in arctic, alpine, and arid/semi‐arid ecosystems around the world, yet our understanding of the belowground impacts of this phenomenon is limited. We conducted a globally distributed field study of 13 alpine sites across four continents undergoing woody plant encroachment and sampled soils from both woody encroached and nearby herbaceous plant community types. We found that woody plant encroachment influenced soil microbial richness and community composition across sites based on multiple factors including woody plant traits, site level climate, and abiotic soil conditions. In particular, root symbiont type was a key determinant of belowground effects, as Nitrogen‐fixing woody plants had higher soil fungal richness, while Ecto/Ericoid mycorrhizal species had higher soil bacterial richness and symbiont types had distinct soil microbial community composition. Woody plant leaf traits indirectly influenced soil microbes through their impact on soil abiotic conditions, primarily soil pH and C:N ratios. Finally, site‐level climate affected the overall magnitude and direction of woody plant influence, as soil fungal and bacterial richness were either higher or lower in woody encroached versus herbaceous soils depending on mean annual temperature and precipitation. All together, these results document global impacts of woody plant encroachment on soil microbial communities, but highlight that multiple biotic and abiotic pathways must be considered to scale up globally from site‐ and species‐level patterns. Considering both the aboveground and belowground effects of woody encroachment will be critical to predict future changes in alpine ecosystem structure and function and subsequent feedbacks to the global climate system. Abstract : Global change is driving woody plant encroachment in arctic, alpine, and arid ecosystems, yet our understanding of the belowground impacts of this phenomenon is limited. We conducted a field study at 13 alpine sites across four continents undergoing woody plant encroachment in the last 50 years. Woody encroachment impacted soil microbial richness and community composition across sites based on multiple factors including woody plant leaf traits, site‐level climate patterns, root symbiont types, and shifts in abiotic soil conditions, emphasizing that multiple biotic and abiotic pathways must be considered to scale up globally from site‐ and species‐level patterns.